Extraterritorial reach of competition remedies. Issue 2 (January 2019) - Harris, Maxwell; Duarte, Maria; Raftery, Colin; Thompson, Alistair; Jewell, Michael
Abstract : This article (which is based on a Competition and Markets Authority submission to an OECD Roundtable on the Extraterritorial Reach of Competition Remedies) considers the role of extraterritorial remedies in UK merger control. The UK Courts have confirmed that the CMA is able to extend its jurisdiction in relation to remedies over conduct outside the UK in certain defined circumstances. This supports the CMA's ability to protect UK consumers in a globalized economy. Notwithstanding these powers, the CMA may take the additional risks that can arise around the implementation of extraterritorial remedies into account, where relevant, when designing remedies. In the CMA's experience, the challenges involved in designing and implementing extraterritorial remedies can best be addressed by close co-operation between different jurisdictions' competition authorities.